Executive Committee Minutes 2019-10-03 - Academic Senate:::::::::
Agenda – Approved. Minutes of 9/19/19 – Approved. Chair Report. President Report. Provost Report. Statewide Senator Report. Vice Chair Report. Vice President of Administration and Finance Report. Associated Students Report. Feedback on Statewide Ethnic Studies requirement. From EPC: Offsite Programs – Approved for Senate Consent Calendar. Version 2 – Lecturer Conversion Presentation. Senate Agenda Approved. APARC Report. FSAC Report. SAC Report.